THE IMAGE OF THE INTELLECTUAL DETECTIVE IN NOVELS OF AGATHA CHRISTIE - Abdujabborova Robiyabegi Jasur qizi, Tohirova Dilrabo Muzaffar qizi (International Journal of Literature and Language Studies, 2026)
The intellectual detective as represented by Hercule Poirot and Miss Marple is the focus of this article, which examines the cognitive and psychological foundations of finding in Agatha Christie’s novels. This article addresses the dual model of intellectual inquiry in Christie’s works, where logical reasoning and intuitive understanding coexist but are rarely analyzed together. The aim of the study is to define the narrative and psychological mechanisms through which Christie constructs the image of the intellectual detective and to compare the distinct problem-solving strategies of her two most famous main characters. The research tasks include analyzing Poirot’s method based on logic, order, and rational deduction, examining Miss Marple’s reliance on intuition and knowledge of human nature, and identifying their roles in the development of the plot and thematic structure. The study applies an interpretative approach and comparative analysis as its main methods.